Neurological and Neurobehavioral Disorders Associated with Toxoplasma gondii Infection in Humans - Maxwell A. Virus; Evie G. Ehrhorn; LeeAnna M. Lui; Paul H. Davis (Journal of Parasitology Research)
The intracellular parasite Toxoplasma gondii is estimated to infect up to 30% of the world population, leading to lifelong chronic infection of the brain and muscle tissue. Although most latent T. gondii infections in humans have traditionally been considered asymptomatic, studies in rodents suggest phenotypic neurological changes are possible. Consequently, several studies have examined the link between T. gondii infection and diseases such as schizophrenia, epilepsy, depression, bipolar disorder, dysphoria, Alzheimer’s disease, Parkinson’s disease, and obsessive-compulsive disorder (OCD). To date, there is varying evidence of the relationship of T. gondii to these human neurological or neurobehavioral disorders. A thorough review of T. gondii literature was conducted to highlight and summarize current findings. We found that schizophrenia was most frequently linked to T. gondii infection, while sleep disruption showed no linkage to T. gondii infection, and other conditions having mixed support for a link to T. gondii. However, infection as a cause of human neurobehavioral disease has yet to be firmly established.